Study of texture properties rejuvenation for aged rice kernel - Maichoon Pisut; Choomjaihan Prasan (BIO Web of Conferences)
Aged rice (stored > 3 months) undergoes significant texture changes, especially hardness and stickiness. Hardness increases, while stickiness decreases with aging. Rice grains were subjected to heat treatment using three different methods: hot air oven (HA), infrared (IR) and microwave (MW). The HA and IR applied heat at a temperature of 100°C, while the MW applied heat at a power of 800 watts. The heat treatment was applied for 3, 4, and 5 minutes. As a result, the hardness of aged rice treated with HA and IR was effectively reduced to 17.79±2.38 N and 17.73±1.26 N, respectively. In contrast, the MW exhibited a lesser reduction in hardness, reaching to 22.82±2.32 N. Regarding stickiness, no statistically significant differences were observed (p < 0.05). Furthermore, hardness exhibited a decreasing with increasing heating time. Additional parameters, Whiteness, transparency and Volume expansion, were also evaluated. Whiteness values were observed to exhibit an increase for all treatments, in contrast to transparency values, which demonstrated a decrease. Volume expansion values, on the other hand, displayed a stable trend, with the exception of MW treated samples, where a statistically significant increase (p < 0.05) was observed.